STUDENTS’ RESPONSE TOWARD CORRECTIVE FEEDBACK IN SPEAKING ACTIVITIES: THE CASE OF UNDERGRADUATE EFL LEARNERS IN SUKOHARJO - Arin Arianti (Proceeding of International Conference on Art, Language, and Culture, 2019)
Giving feedback is one of the important steps in improving learners’ progress in speaking. It is important for students to know how well they are doing as they learn. The objective of this study is to explore the students’ response for feedback that they receive in Speaking class. Its subjects were 25 students of English Department in Veteran Bangun Nusantara University of Sukoharjo. Observation and interview were used to its data and the data were analysed qualitatively. The result of this study showed that the students’ response for feedback that they receive in Speaking class was taking positive response for repairing and need repairing uptake.STUDENTS’ RESPONSE TOWARD CORRECTIVE FEEDBACK IN SPEAKING ACTIVITIES: THE CASE OF UNDERGRADUATE EFL LEARNERS IN SUKOHARJO